2018
DOI: 10.2147/ndt.s172933
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and risk of dementia: a meta-analysis study

Abstract: BackgroundEvidence suggests that schizophrenia may be associated with an increased risk of dementia, but results from prior studies have been inconsistent. This study aimed to estimate the relationship between schizophrenia and incident dementia using a quantitative meta-analysis.MethodsSeveral databases were used to gather relevant information, including PubMed, Embase, and Web of Science, with the publication date of articles limited up to December 23, 2017. All studies reported a multivariate-adjusted estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 68 publications
5
66
1
2
Order By: Relevance
“…For example, the higher prevalence of paranoid schizophrenia among cases in which benzodiazepine may be used for the treatment may lead to a higher benzodiazepine prevalence and consequent ROR overestimation. 36 Although we adjusted the comorbidities in the outcome model, the imbalance of confounders between cases and non-cases may have resulted in ROR overestimations. Cognitive decline and dementia can be clinically different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the higher prevalence of paranoid schizophrenia among cases in which benzodiazepine may be used for the treatment may lead to a higher benzodiazepine prevalence and consequent ROR overestimation. 36 Although we adjusted the comorbidities in the outcome model, the imbalance of confounders between cases and non-cases may have resulted in ROR overestimations. Cognitive decline and dementia can be clinically different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with schizophrenia (SZ) are at risk for elevated aging-related functional and neurological decline, termed accelerated aging (Kirkpatrick et al, 2008;Ito and Barnes, 2009;Jeste et al, 2011;Kochunov et al, 2013bKochunov et al, , 2016b. They are at significantly higher risks (1.5 to 5 times) for developing cognitive deficits and dementia before age (Cai and Huang, 2018;Chen et al, 2015;Diniz et al, 2017;Ribe et al, 2015). Previous studies demonstrated that the integrity of the cerebral white matter as measured by fractional anisotropy (FA) in diffusion weighted imaging (DTI), declined in SZ patients at nearly twice the aging rate of normal controls (Mori et al, 2007;Friedman et al, 2008;Kochunov et al, 2013aKochunov et al, , 2013bWright et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the prescription of Zotepine may indicate early AD symptoms and, consequently, an increasing likelihood of incident AD. Alternatively, some studies indicate that individuals with schizophrenia may have an increased risk for the development of dementia 32 . Given this, it might be possible that incident AD is high in individuals with schizophrenic symptoms to whom Zotepine is prescribed.…”
Section: Discussionmentioning
confidence: 99%